Kings falling [large type] - Kendig, Ronie (Kendig, Ronie. Book of the wars, 2020)
"On a mission to recover the Book of the Wars, Leif and his team are diverted by a prophecy that foretells of sinister guardians who will decimate the enemies of the ArC. As they try to stop the guardians, danger creeps closer to home. The implications could tear them apart"--Provided by publisher.